Please answer this question.?
Attachments:
![](https://hi-static.z-dn.net/files/df3/595f19e8fc5483c670a0ba2f9a7b2fc2.jpg)
Answers
Answered by
1
Answer:-
Given Expression,
2x² + 2x - 12 = 0
Dividing the equation by 2 we get,
x² + x - 6 = 0
x² + 3x - 2x - 6 = 0
x ( x + 3 ) - 2 ( x + 3 ) = 0
( x+ 3 ) ( x - 2 ) = 0
x = -3 , x = 2
1. We will reject (A) because x cannot be bigger than 3.
2. We will reject (D) because x cannot be bigger than 2 or smaller than -3.
Option (B) & (C) both are correct because in both case we will get the positive root 2
Answered by
0
Answer:
Didi I was feeling bored so I told
Similar questions